Knjige, ki niso smele iziti - Smolik, Marijan (Knjižnica, 2004)
The author finds that the bibliographic collection of the Slovene religious print of the Seminary Library in Ljubljana contain data on books which were tohave been published by the end of World War II, some had even been printed but were never published. Some examples of these books are presented in the article.
Keywords: bibliografije; verski tisk; cenzura; svoboda tiska; zgodovinski pregledi; založništvo; knjigotrštvo